9-(4p-3)+p=36

Simple and best practice solution for 9-(4p-3)+p=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-(4p-3)+p=36 equation:


Simplifying
9 + -1(4p + -3) + p = 36

Reorder the terms:
9 + -1(-3 + 4p) + p = 36
9 + (-3 * -1 + 4p * -1) + p = 36
9 + (3 + -4p) + p = 36

Combine like terms: 9 + 3 = 12
12 + -4p + p = 36

Combine like terms: -4p + p = -3p
12 + -3p = 36

Solving
12 + -3p = 36

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -3p = 36 + -12

Combine like terms: 12 + -12 = 0
0 + -3p = 36 + -12
-3p = 36 + -12

Combine like terms: 36 + -12 = 24
-3p = 24

Divide each side by '-3'.
p = -8

Simplifying
p = -8

See similar equations:

| (n-9)*9=90 | | n-9*9=90 | | 2x=x-36 | | 4+6x+12-3x= | | 8a-(5a+1)=8-2(a-3) | | 9(y-5)=7y-37 | | 16x^2-4x-4=0 | | (6a^2+5a)(-12a+2)=0 | | N-14=15 | | 13589989+259003-145690= | | 12x-56=63x | | 90=x+x*0.25 | | 2.x-3=9 | | 3x-1=-17 | | (4x-3)(x+1)=0 | | 5x-50=x+90 | | 149-3x=24x+17 | | 4(r-7)+1=5(r+3)-25 | | 5(3+x)-4(x+1)=2 | | 6y-4=35+6y | | 2(x+3)+4(x-1)=1 | | 6(q-2)=9 | | 22x+6=-90-10x | | 7+7x=14x-14 | | 4x+7/8=5x-7/8 | | 7+8x=16x-14 | | 7(z+1)=13 | | 9-10x=20x+18 | | 7x-6y=13 | | -8t-3t=-5t-6t | | 9-10x=18x+20 | | 9-10x=5x+20 |

Equations solver categories